(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2025)
This study is motivated by the gap between curriculum demands that emphasize student-centered learning and field practices that are still dominated by teacher-centered approaches. The study aims to analyze the nature of students conceptually and its implications for formulating effective learning planning. The research method uses a literature study that examines development theories, philosophy of education, Islamic education perspectives, and empirical findings related to the role of students in the learning process. Data collection was conducted by searching for literature using specific keywords and selecting relevant and reliable sources from the Google Scholar database. The collected data were then analyzed using content analysis. The study results indicate that learners are unique individuals with cognitive, socio-emotional, and learning experience differences that affect how they understand material. Understanding these characteristics directly impacts the selection of teaching strategies, including the use of differentiated approaches, active learning, experiential learning, as well as the utilization of interactive media that encourages student engagement. The research also found that the implementation of learner-centered teaching still faces obstacles such as limited teacher competence, heterogeneous student abilities, and structural barriers in schools.